A historical overview of ethnobotanical data in Albania (1800s-1940s) - Saraçi, Anyla; Damo, Robert (Ethnobiology and Conservation, 2020)
This paper is an historical review of ethnobotanical notes about wild and cultivated edible plants collected through texts from the end of the 18th century (1796) to the first decades of the 20th century (1930) in the area of Albania under European Turkey, which included parts of today North Macedonia and Kosovo. Albania is an Eastern European country, which has been little studied from historical ethnobotany point of view. For this reason, this paper is focused on foreign authors’ works containing data on the use of plants for economic, medicinal, food purposes, and discussing mythological, religious and magical explanations for them. The study is not intended to be an exhaustive review of all materials on this subject, but includes the texts known to us that contain ethnobotanical knowledge. Further scientific research can be carried out in other studies on historical ethnobotany not only by foreign authors but also by Albanians.